Pediatric nasal reconstruction with frontal flap: a case report - Guevara Valmaña, Osvaldo Ivan; Apellaniz Campo, Armando G.; Gaspar, Daniel Angeles; Leyva Sotelo, Leslie M.; Chavez Serna, Enrique; Delgado, Laura Andrade (International Journal of Research in Medical Sciences, 2019)
Authors presented the case of a 4-year-old male patient who suffered a dog bite on his face with partial amputation of the nasal tip, managed at another institution conservatively, so that one year after the injury he came for the nasal deformity. A frontal flap was performed for reconstruction achieving excellent results, coverage was achieved with similar characteristics of the skin as color and texture. The patient had a follow-up of 5 years with an appropriate course. Authors presented the case due to few reports in the literature of its use in children, where it can be observed that it is an excellent reconstructive tool.